(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
This article discusses reforms in the field of tourism. The tools for increasing the potential of tourism in the region are expressed in the article. Particular attention is paid to the fact that tourism is a separate field and the existence of forces in its formation. The importance of the article is measured by the clear coverage of the means of increasing the potential of tourism